Electrical and optical properties of transparent conducting In4+xSn3-2xSbxO12 thin films - Kuznetsov, V; O'Neil, D; Pepper, M; Edwards, P (2011)
Thin films of In4 xSn3-2xSbxO12 (0≤x ≤1.0) have been grown on glass substrates by pulsed laser deposition. High resolution transmission electron microscopy and x-ray diffraction confirmed the polycrystalline nature of the films with a typical grain size of 20-60 nm. Surface analysis by x-ray photoemission spectroscopy demonstrated that the surface region of the films is non-stoichiometric, being significantly rich in tin and antimony and deficient in both indium and oxygen. Both electron mobility and carrier concentration steeply decrease with increasing antimony content in the films. The temperature dependence of the electrical transport properties was explained by a model in which for x ≥ 0.5, the carrier transport is governed by percolation conduction over the distribution of potential barriers around the conduction band edge while degenerate electronic conduction is attained at x <0.5. The optical bandgap value decreases from 3.15 to 2.92 eV with increasing antimony content from 0 to 1. © 2011 American Institute of Physics.